The ideologies of the Octagon the Ultimate Fighting Championship as a manifestation of the postmodern phenomenon - Berame, Janyn P. (2013)
The postmodern moment creates paranoia in the grand narratives of patriarchy, masculinity, and heteronormativity. This paranoia is called pomophobia, the fear of the shift the postmodern moment created and continues to create in the hegemony. In response, the dominant views, particularly patriarchy, have regrouped themselves and created hegemonic masculinity present in athleticism, especially male-driven sports such that of Mixed Martial Arts. This study looks closely at Mixed Martial Arts (MMA) as portrayed in the Ultimate Fighting Championship (UFC) and how its components exhibit self-reflexivity, to the point that it asserts rebuttals to the very ideologies it advocates. This study looks at MMA in UFC as a counter proposal to the meta-narratives of patriarchy and the universality of truths and how it manifests the postmodern phenomenon.
Includes bibliographical references (pages 95-96).
Keywords: Mixed martial arts; Postmodernism; Ultimate Fighting Championship (Organization).; Masculinity